70 years of bilirubin sensing: towards the point-of-care bilirubin monitoring in cirrhosis and hyperbilirubinemia. Issue 5 (25th August 2022) - Ndabakuranye, Jean Pierre; Li, Shiqiang; Burchall, Genia; Fox, Kate; Piva, Terry; Xu, Zhangyu; Kavehei, Omid; Prawer, Steven; Ahnood, Arman
Abstract : We provide a perspective on monitoring the blood bilirubin concentration using simple methods, which are economical and can be adopted in point of care settings. These are a homecare test system, a miniature implant, and a neonatal wearable patch. Abstract : Bilirubin is clinically confirmed as a biomarker for liver health and has been utilized to implement the prognostic systems for cirrhosis and hyperbilirubinemia. Optical and chemical methods have been developed and are widely used to determine blood bilirubin levels within clinical settings. However, due to their instrument complexity, high cost, and space requirements, the existing bilirubinometric technologies do not lend themselves to point-of-care (PoC) applications within the community settings or for real-time monitoring. Consequently, bilirubin monitoring can only be monitored intermittently, resulting in missed episodes that may otherwise require clinical interventions. This review paper aims to explore potential strategies for real-world point-of-care applications. Part one discusses the metabolic pathway of bilirubin and the epidemiology of liver cirrhosis and neonatal hyperbilirubinemia. Part two provides a comprehensive review of existing bilirubinometric techniques and highlights the need for point-of-care bilirubin monitoring. Part three develops a theoretical framework for bilirubin spectroscopy. It explores two potential bilirubin measurement approaches: the multiwavelength (based on the distinct optical signatures of bilirubin) and the photodegradation kinetics approach (which relies on bilirubin degradation under blue light irradiation). Part four outlines future recommendations and provides a perspective towards three possible PoC bilirubin measurement devices for real-world applications, including a homecare testing system, a miniature implant and a neonatal wearable patch. These devices provide an opportunity for extending the reach of bilirubin measurement in locations outside hospitals and clinics.